Finger lickin' fifteen - Evanovich, Janet (New York : St. Martin's Press, 2009)
While recovering from an ill-timed makeup mishap, Lula is a witness to celebrity chef, Stanley Chipotle, losing his head--literally. Now Lula and Stephanie are on the hunt to identify the killers before Lula is next on the chopping block. Meantime, Ranger's recruited Stephanie's help for a top secret mission. Someone on the inside at Rangeman is leaking client information, determined to bring the company down. Can Stephanie hunt down a killer, a traitor, and keep Grandma out of the sauce?
edited hb 2015-06-16
Keywords: Bail bond agents -- New Jersey -- Trenton -- Fiction; Cooks -- Crimes against -- Fiction; Plum, Stephanie (Fictitious character) -- Fiction; Police -- New Jersey -- Fiction; Women bounty hunters -- Fiction; New Jersey -- Fiction; Trenton (N.J.) -- Fiction; Humorous fiction; Mystery fiction